"Tanto por ser mulher, quanto por ser estrangeira" : lutas por reconhecimento e formas de resistência de mulheres migrantes no Brasil - Paula Dias Dornelas (2020)
The work investigates the struggles for recognition and the forms of resistance adopted by migrant women living in Brazil. The aim is to understand how situations of disrespect affect the way women from Latin American and Caribbean countries perceive themselves as migrants and how they resist injustice. Based on the Theories of and discussions on forms of resistance and migrant struggles, the idea is to reflect on processes and social relations developed by women, whether in their families, friends, within other migrants, and with institutional actors where they live. Through an interpretative approach, the research demonstrates how situations of disrespect permeate the trajectories of migrant women in Brazil. Experiences of xenophobia, sexism and racism are present issues, whether in work dynamics, public spaces or family experiences. The forms of resistance also cross the most varied spheres, reflecting on daily strategies of resistance and collective forms of struggle, such as the formation of groups and collectives of women in their destination places.